The Correlation Between Circulating Ghrelin and Insulin Resistance in Obesity: A Meta-Analysis - Zhang, Cai-Shun; Wang, Liu-Xin; Wang, Rui; Liu, Yuan; Song, Li-Min; Yuan, Jun-Hua; Wang, Bin; Dong, Jing (Frontiers in Physiology, 2018)
Background: Ghrelin, a peptide mainly produced by stomach X-A cells. It plays a pivotal role in the regulation of food intake and energy metabolism, including glucose metabolism and insulin sensitivity. However, the correlation between circulating ghrelin levels and insulin resistance in obesity remained uncertain. This meta-analysis aimed to clarify the association between ghrelin and IR in obesity. Methods: A systematic literature search was performed using PubMed, EMBASE, Cochrane Library and Web of Science until April 18, 2018 with the keywords “ghrelin” and “insulin resistance.” Two independent reviewers selected studies and assessed data. Subgroup analyses were performed to search for sources of heterogeneity. Funnel plots and Egger's test were used to detect publication bias. A random-effects model was used to calculate the pooled effect size. Results: Ten studies with 546 participants were included in this meta-analysis. We found that ghrelin levels were negatively correlated with IR in obese individuals. (r = −0.31; 95% CI: −0.45 to −0.18). Subgroup analysis revealed that circulating ghrelin levels were significantly negatively correlated with IR in people with normal fasting blood glucose (FBG) (<6.9 mmol/dl) (r = −0.28; 95% CI: −0.47 to −0.09, I2 = 39.5%), while there was no relationship between circulating ghrelin levels and IR in the high FBG group (>6.9 mmol/dl) (r = −0.15; 95% CI: −0.33 to 0.03, I2 = 0.0%). Publication bias was insignificant (Egger's test: P = 0.425). Conclusion: In obesity, circulating ghrelin levels were significantly negative correlated with insulin resistance in individuals with normal fasting blood glucose.